2019
DOI: 10.1002/zaac.201800454
|View full text |Cite
|
Sign up to set email alerts
|

A New Fluorescent Probe for Selective Cd2+ Detection and Cell Imaging

Abstract: A new highly selective fluorescent probe, (E)-4-(4-([2,2Ј:6Ј,2ЈЈ-terpyridin]-4Ј-yl)styryl)-1-octadecylpyridin-1-ium bromide (ZC-F8), was designed and synthesized for cadmium detection and cell imaging. The fluorescence spectra of ZC-F8 exhibited its excellent response towards Cd 2+ via intramolecular charge transfer effect and * Dr. W. Lin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…It has been reported in the published papers that functional group with N and O atoms can coordination with antimony and force the change of signals in the detection system , . So it could be suggested that the detection of antimony by TPE‐2IPH was owing to the formation of TPE‐2IPH aggregates forced by the coordination between the functional group IPH and antimony.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in the published papers that functional group with N and O atoms can coordination with antimony and force the change of signals in the detection system , . So it could be suggested that the detection of antimony by TPE‐2IPH was owing to the formation of TPE‐2IPH aggregates forced by the coordination between the functional group IPH and antimony.…”
Section: Resultsmentioning
confidence: 99%
“…As to the chromophore, tetraphenylethylene (TPE) with aggregation induced emission (AIE) property is an ideal choose. Since discovered in 2001, TPE derivatives had been widely used in the detection of heavy metal irons such as Cu II , Hg II , Cd II and so on . On the other hand, it has been reported that functional group with N and O atoms could combine with antimony specificity,, so salicylaldehyde with reactive hydroxyl and aldehyde groups is hopefully to be the functional group.…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials for diagnosis or therapy have been investigated for decades . Nowadays, the photodynamic therapy (PDT) has been receiving great attention in cancer treatments .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the construction of chiral coordination polymers has attracted enormous interest as functional materials for potential applications in enantiomeric separation,, asymmetric catalysis,, fluorescence, nonlinear optics, and so on. In particular, luminescent chiral coordination polymers have become more focused as chemosensors for the probe of metal cations, small organic molecules and nitro explosives due to their easy operation, high selectivity and sensitivity …”
Section: Introductionmentioning
confidence: 99%